High pressure thermal inactivation of Clostridium botulinum type E endospores – kinetic modeling and mechanistic insights - Lenz, Christian A.; Reineke, Kai; Knorr, Dietrich; Vogel, Rudi F. (Frontiers in Microbiology, 2015)
Cold-tolerant, neurotoxigenic, endospore forming Clostridium (C.) botulinum type E belongs to the non-proteolytic physiological C. botulinum group II, is primarily associated with aquatic environments, and presents a safety risk for seafood. High pressure thermal (HPT) processing exploiting the synergistic effect of pressure and temperature can be used to inactivate bacterial endospores. We investigated the inactivation of C. botulinum type E spores by (near) isothermal HPT treatments at 300 – 1200 MPa at 30 – 75 °C for 1 s – 10 min. The occurrence of heat and lysozyme susceptible spore fractions after such treatments was determined. The experimental data were modeled to obtain kinetic parameters and represented graphically by isoeffect lines. In contrast to findings for spores of other species and within the range of treatment parameters applied, zones of spore stabilization (lower inactivation than heat treatments alone), large heat susceptible (HPT-induced germinated) or lysozyme-dependently germinable (damaged coat layer) spore fractions were not detected. Inactivation followed 1st order kinetics. DPA release kinetics allowed for insights into possible inactivation mechanisms suggesting a (poorly effective) physiologic-like (similar to nutrient-induced) germination at ≤ 450 MPa/≤ 45 °C and non-physiological germination at >500 MPa/>60 – 70 °C. Results of this study support the existence of some commonalities in the HPT inactivation mechanism of C. botulinum type E spores and Bacillus spores although both organisms have significantly different HPT resistance properties. The information presented here contributes to closing the gap in knowledge regarding the HPT inactivation of spore formers relevant to food safety and may help industrial implementation of HPT processing. The markedly lower HPT resistance of C. botulinum type E spores than spores from other C. botulinum types, could allow for the implementation of milder processes without endangering food safety.